The hospital triage in emergency services - Vásquez-Alva, Rolando (2019)
Hospital Triage is a fundamental part of emergency clinical management when the demand exceeds the availability of human and technical resources. The Emergency Triage is a system that offers a method to assign clinical priority in emergency situations. It is not designed to judge whether patients are properly diagnosed in the emergency setting, but to ensure that those who need urgent care receive it properly and in a timely manner.Through the implementation of triage in emergencies, there has been an improvement in the quality of care, since it is attended in an appropriate manner and in the time necessary to those pathological situations that require rapid assistance.Triage in emergency services has been evaluated in many research projects where they conclude that it is necessary to create, develop and change it according to the demands of better care and increased demand in emergency. This last aspect has been the most important determinant worldwide in the development and creation of different triage scales to deal with emergencies adequately and in the necessary time. In Peru in general and in Lima in particular, there is no systematic development of concepts and uniform implementation of triage in hospital emergency services. It is necessary to know the concepts surrounding the triage of hospital emergency services and in accordance with this, establish the regulations, by the governing bodies in health, necessary to improve initial care and emergency quality.   DOI 10.25176/RFMH.v19.n1.1797